Hydrothermal Synthesis of Hierarchical Flower-Like Sn3O4 Nanomaterial for High-Photocatalytic Properties. (6th August 2020) - Liao, Lei; Huang, Weigang; Cai, Fanggong; Lv, Chenghang; Qin, Ba; Zhang, Qinyong
Abstract : Nanostructured tin oxide has drawn extensive attention from researchers as a semiconductor, owing to its unique physicochemical properties. In this study, a mixed-valence tin oxide, hierarchical flower-like Sn3 O4 self-assembled with numerous nanosheets was successfully synthesized using a simple hydrothermal process. The structure, morphology, and specific surface area were characterized using X-ray diffraction (XRD), a scanning electron microscope (SEM), and an automatic surface area analyzer, respectively. The obtained Sn3 O4 products had hierarchical nanostructures and uniform flower-like morphology. The diameter of this flower ranged from 300 nm to 2.6 μ m. The flower-like Sn3 O4 was self-assembled by nanosheets with a thickness of 8 ∼25 nm. By controlling the temperature of hydrothermal reaction and the concentration of surfactant, the as-synthesized hierarchical flower-like Sn3 O4 (Sn3 O4 −25SC) can obtain the largest specific surface area of approximately 66 m 2 ∙g −1, and thus exhibits excellent photocatalytic activity while degrading the methylene blue (MB) aqueous solution under UV light irradiation. Results show that the degradation rate of dye MB can reach 97% within 60 min. Moreover, a possible growth mechanism of the flower-like architectures was proposed. Sodium citrate promotes the growth of Sn3 O4 nanosheets and accelerates the self-assembling of nanosheets into flower-like architecture.